NAVIGATING NIGERIA’S CHANGING AGRO-ECOLOGICAL REALITIES THROUGH CLIMATE-SMART AGRICULTURE FOR ENHANCED FOOD SECURITY - NguumburVande, Ukohol F Y; Iorbee, Ahwen Andrew; Sesugh, Uker (Advanced Journal of Environmental Sciences (AJES), 2025)
This work, Navigating Nigeria’s Changing Agro-Ecological Realities through Climate-Smart Agriculture for Enhanced Food Security, investigates the multifaceted impact of climate change on agriculture in Nigeria and evaluates the role of Climate-Smart Agriculture (CSA) as a mitigation and adaptation strategy. Guided by the Sustainable Livelihood Framework (SLF) and Systems Theory, this research underscores how agricultural systems are dynamically influenced by climate variability and socioeconomic structures. Employing a qualitative-descriptive methodology, data were sourced from relevant literature, institutional reports, and policy documents to assess the effectiveness and adoption challenges of CSA practices across Nigeria’s agro-ecological zones. Findings reveal that rising temperatures, erratic rainfall, and extreme weather events—such as floods and droughts—are severely disrupting agricultural productivity, particularly in the northern and coastal regions. Crop failures, livestock mortality, and resource conflicts are compounding food insecurity and rural poverty. CSA practices—such as conservation agriculture, agroforestry, and drought-tolerant crops—have shown promise in improving resilience, especially in the Kaduna and Katsina States. However, adoption remains low because of cultural resistance, limited access to finance, poor infrastructure, and policy fragmentation. The study concludes that CSA presents a transformative and people-centered approach to climate adaptation and food security in Nigeria. However, its success hinges on institutional coherence, rural infrastructure investment, and inclusive governance. The study recommends, among other things, the integration of CSA principles into national agricultural extension programmes.